Acid‐Triggered O−O Bond Heterolysis of a Nonheme FeIII(OOH) Species for the Stereospecific Hydroxylation of Strong C−H Bonds. Issue 20 (16th January 2018) - Serrano‐Plana, Joan; Acuña‐Parés, Ferran; Dantignana, Valeria; Oloo, Williamson N.; Castillo, Esther; Draksharapu, Apparao; Whiteoak, Christopher J.; Martin‐Diaconescu, Vlad; Basallote, Manuel G.; Luis, Josep M.; Que, Lawrence; Costas, Miquel; et al.
Abstract: A novel hydroperoxoiron(III) species [Fe III (OOH)(MeCN)(PyNMe3 )] 2+ (3 ) has been generated by reaction of its ferrous precursor [Fe II (CF3 SO3 )2 (PyNMe3 )] (1 ) with hydrogen peroxide at low temperatures. This species has been characterized by several spectroscopic techniques and cryospray mass spectrometry. Similar to most of the previously described low‐spin hydroperoxoiron(III) compounds, 3 behaves as a sluggish oxidant and it is not kinetically competent for breaking weak C−H bonds. However, triflic acid addition to3 causes its transformation into a much more reactive compound towards organic substrates that is capable of oxidizing unactivated C−H bonds with high stereospecificity. Stopped‐flow kinetic analyses and theoretical studies provide a rationale for the observed chemistry, a triflic‐acid‐assisted heterolytic cleavage of the O−O bond to form a putative strongly oxidizing oxoiron(V) species. This mechanism is reminiscent to that observed in heme systems, where protonation of the hydroperoxo intermediate leads to the formation of the high‐valent [(Porph . )Fe IV (O)] (Compound I). Abstract : Reaction of a novel Fe III (OOH) species with acid makes this species capable of hydroxylating strong C−H bonds in a stereospecific manner. Stopped‐flow kinetic analyses and theoretical studies provide a rationale for the observed chemistry, an acid‐assisted heterolytic cleavage of the O−O bond to form a strongly oxidizing oxoiron(V) species.